Regular noturno: possibilidades de reinvenção: uma experiência em Angra dos Reis - Brito, Sandra Regina Cardoso de (2008)
In the present work, the author develops a reflection about her doing as an educational guide. She starts from a criticism on the paradigm of modern science, to situate the implications of a research with the daily life, understood as “ time-space” of production of the existence and knowledge, creeds and values that give sense and direction; a “ time- space” in what nets of subjectivenesses are built, forging multiple identities. Narrating her experience from the network listening to words said in distinct forms in daily life, sewing the history and memory threads that reside the Regular Night Education of Municipal School Cacique Cunhãbebe, in Angra dos Reis. In the movement of reflection on the research, the author assumes herself as subject of the her process of permanent formation, placing herself to favor the constitution of new relationships at school, based on emancipation processes, in what all subjects involved in the daily life network are polite and freed in communion, in an incessant quest for the shared authority in the processes of curricular organization, where curriculum is understood as daily life creation of the subjects who make the school a practice that involves knowledges and processes.